DESIGN, FORMULATION AND IN VITRO DRUG RELEASE FROM TRANSDERMAL PATCHES CONTAINING IMIPRAMINE HYDROCHLORIDE AS MODEL DRUG - Hardainiyan, Swati; Kumar, Krishan; Nandy, Bankim Chandra; Saxena, Richa (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: The aim of the present investigation was to form matrix type transdermal patches containing imipramine hydrochloride were prepared using two polymers by solvent evaporation technique to minimise the dose of the drug for lesser side effect and increase the bioavailability of a drug. Methods: In the present study, drug loaded matrix type transdermal films of imipramine hydrochloride were prepared by the solvent evaporation method with the help of polymers along with polyethene glycol (PEG) 400 was used as plasticizer and dimethyl sulfoxide (DMSO) was used as penetration enhancer. Drug-polymer interactions determine by FTIR and a standard calibration curve of imipramine hydrochloride was determined by using UV estimation. Results: The formulated transdermal patch by using PVP K-30, HPMC K100M showed good physical properties. All prepared formulations indicated good physical stability. The formulation F-1 gave the most suitable transdermal film with all desirable physicochemical properties. The thickness of the patches was varied from 0.263±0.67 mm to 0.301±0.61 mm, uniformity of patches showed that patches prepared by solvent evaporation while low standard deviation values ensued by thickness measurements of the film, and weights ranged between 50.5±0.75 mg and 52.15±2.15 mg, which indicates that different batches patch weights, were comparatively similar. Folding endurance was found to be>200 that is satisfactory for the patches, drug content was found to be 5.33±0.14 mg to 5.57±0.095 mg. In vitro, drug permeation studies of formulations were performed by using K-C diffusion cells using abdomen skin of the albino rat. The results were best in in-vitro skin permeation through rat skin as compared to all other formulations prepared with a hydrophilic polymer containing permeation enhancer. The formulation, F1 is considered as the best formulation, since it shows maximum in vitro drug release as 84.71±3.07 % at 24 h. The drug release kinetics studies showed that the majority of formulations were governed by Higuchi model and mechanism of release was non-Fickian mediated. Conclusion: In conclusion, controlled release transdermal drug delivery system (TDDS) patches of imipramine hydrochloride can be prepared using the polymer combinations, with plasticizer and enhancer. The release rate of drug through patched increased simultaneously as the concentration of hydrophilic polymer was increased. However, the mechanism of drug release of all formulations was non-Fickian. The properties of a film did not change during the period of study.